Biomechanical effects of different mandibular movements and torque compensations during mandibular advancement with clear aligners: a finite element analysis - Wang, Ya; Daraqel, Baraa; Wang, Ying; Yang, Dan; Dong, Yihan; Hu, Yun; Zheng, Leilei (Frontiers in Bioengineering and Biotechnology, 2024)
This study aimed to evaluate the biomechanical effects of different mandibular movements and torque compensation during mandibular advancement with clear aligners using finite element analysis. Methods: Models were constructed to include the mandible, teeth, periodontal ligament (PDL), and clear aligners with buccal wings. Five oral muscles (superficial masseter, deep masseter, medial temporalis, posterior temporalis, and medial pterygoid) were represented as springs. Muscle values were measured and applied during different mandibular movements, including advancement distances (1-7 mm) and occlusal opening distances (2-4 mm). Different torque compensation angles (0°, 1°, 2°, and 3°) were applied to the mandibular central incisor. Results: When the mandibular advancement was equal to or slightly excessed the occlusal opening distance, stress on the posterior PDL decreased and became more evenly distributed. Increasing the occlusal opening distance significantly raised stress on the posterior PDL and caused grater labial inclination of the mandibular anterior teeth. As the torque compensation increased, the labial inclination of the mandibular central incisor decreased, but stress on the PDL increased. Nearly complete bodily movement of the lower central incisor was achieved with torque compensation angles of approximately 15°, 19°, and 20° in models M1-2, M2-3, and M3-4, respectively. Conclusion: To maintain periodontal health during mandibular advancement, it is recommended that the mandibular advancement distance be equal to or slightly excessed the occlusal opening distance. Excessive occlusal opening distance increases stress on the posterior PDL and the labial inclination of mandibular anterior teeth, requiring careful control. Additionally, proper torque control of the mandibular interior teeth is crucial for optimal outcomes.